2021
DOI: 10.1002/aenm.202101370
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Argyrodite as Solid Electrolyte and Cathode Precursor for Solid‐State Batteries with Long Cycle Life

Abstract: All‐solid‐state batteries with conversion‐type cathodes promise to exceed the performance of lithium‐ion batteries due to their high theoretical specific energy and potential safety. However, the reported performance of solid‐state batteries is still unsatisfactory due to poor electronic and ionic conduction in the composite cathodes. Here, in situ formation of active material as well as highly effective ion‐ and electron‐conducting paths via electrochemical decomposition of Li6PS5Cl0.5Br0.5 (LPSCB)/multiwalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 59 publications
4
86
0
Order By: Relevance
“…The cell volume expands during the discharge process resulting in a net pressure of ≈0.5 MPa, which is comparable to the conventional cathode materials reports in sulfide‐based all‐solid‐state systems. [ 45 ] Thus, to alleviate the compressive stress and maintain interfacial contact, an external pressure of about 300 MPa was for the electrochemical performance tests of the all‐solid‐state Se–LHC–C/LHC/Li cell. In contrast, the electrochemical behavior without externally applied pressure is also shown in Figure S17, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The cell volume expands during the discharge process resulting in a net pressure of ≈0.5 MPa, which is comparable to the conventional cathode materials reports in sulfide‐based all‐solid‐state systems. [ 45 ] Thus, to alleviate the compressive stress and maintain interfacial contact, an external pressure of about 300 MPa was for the electrochemical performance tests of the all‐solid‐state Se–LHC–C/LHC/Li cell. In contrast, the electrochemical behavior without externally applied pressure is also shown in Figure S17, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Other sulfide SEs also have been found to have similar reversible properties, such as Li 3 PS 4 , 78Li 2 S Á 22P 2 S 5 , LGPS, and Li 6 PS 5 Cl 0.5 Br 0.5 . 65,[152][153][154][155][156][157] In addition to the self-decomposition, the sulfides are also (electro-)chemically unstable to some CAMs (e.g., LiCoO 2 ) due to the mismatch chemical potential. 158 As illustrated in Figure 4F, in the case of the Fermi energy level of the cathode (μ c ) below the electrolyte HOMO, the electrolytes undergo oxidation at the cathode interfaces and thereby form cathode electrolyte interphases (CEI); in contrast, an anode with a μ a above the electrolyte LUMO will reduce the electrolyte to form solid electrolyte interphases (SEI).…”
Section: The Electrochemical Reaction Occurs At Interfacesmentioning
confidence: 99%
“…However, Dewald et al 151 assumed that the formation of crystalline P 2 S 5 was not feasible due to entropic reasons, while the local formation of bridging sulfur (i.e., P–S x –P bonds) was more likely to occur. In addition, Wang et al 152 found that PS 4 3− will convert into P 2 S 7 4− and S (0) , and finally to P 2 S 6 2− and S (0) . Other sulfide SEs also have been found to have similar reversible properties, such as Li 3 PS 4 , 78Li 2 S · 22P 2 S 5 , LGPS, and Li 6 PS 5 Cl 0.5 Br 0.5 65,152–157 …”
Section: Interfacial Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the peaks (★ and ☆) appear, their magnitude increases with further SE oxidation (orange to red curves). The oxidative degradation of Li-thiophosphates leads to amorphous phases with complex P-[S] n -P-type polyanions, e.g., (P 2 S n ), Li 2 S n , Li 3 PS 4 (μ-S n )­S 4 PLi 3 ((Li 3 PS 4 ) 2 S n ), and -[S] n - containing polysulfides. , The more comprehensive descriptions on oxidative and reductive electrolyte degradation are summarized in refs and . In short, a kinetic electrochemical stability window for these electrolytes exists, and once the solid electrolytes are decomposed, their decomposition products become redox-active.…”
Section: Challengesmentioning
confidence: 99%